The Role of Technology in Human Capital and Economic Growth in Indonesia (International Conference of Graduate School on Sustainability (ICGSS), 2021)
The aim of this research is to investigate the direction of the influence of human capital technology and economic growth, testing the direction of the influence of the three variables using vector analysis.The period of this research is from 1995 to 2020. The data analyzed is limited to data recorded by the world bank and is general in nature on a national scale. we found that technology has a role in increasing the influence of human capital on economic growth as well as providing a direct influence on economic growth. However, technology is also influenced by the development of human capital and economic growth. Human capital, technology, and economic growth influence and reinforce each other.